2021
DOI: 10.1155/2021/6622661
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Building Exit Layout: Combining Exit Decisions of Evacuees

Abstract: Exits are essential to the efficiency of building evacuation due to its irreplaceable function, and the layout of multiple exits has always been the key concern for architectural design. To accurately evaluate the evacuation efficiency of different multiexit layouts and optimize the design rules, a dynamic exit decision model integrating an exit selection strategy and the social force model is developed to simulate the practical evacuation. And our proposed model outperforms the original social force model in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…KURDI H A et al, used two artificial intelligence (AI) techniques, simulated annealing (SA) and depth-first search (DFS), to evaluate the evacuation time when the exit is on one side, adjacent side, relative side, and all sides [3]. In addition, MA G et al, evaluated the evacuation performance of different exit layouts in the same room considering evacuation headcount exit decision [22], and the analysis showed that two parallel exits are the most efficient layout among three common exit layouts, and the too large or too small interval between two exits is not conducive to evacuation. XIE Q-M et al, searched for the best door location with the shortest evacuation time in a single room based on polynomial chaos expansion and genetic algorithm considering room occupant density [23].…”
Section: Exit Location Optimizationmentioning
confidence: 99%
“…KURDI H A et al, used two artificial intelligence (AI) techniques, simulated annealing (SA) and depth-first search (DFS), to evaluate the evacuation time when the exit is on one side, adjacent side, relative side, and all sides [3]. In addition, MA G et al, evaluated the evacuation performance of different exit layouts in the same room considering evacuation headcount exit decision [22], and the analysis showed that two parallel exits are the most efficient layout among three common exit layouts, and the too large or too small interval between two exits is not conducive to evacuation. XIE Q-M et al, searched for the best door location with the shortest evacuation time in a single room based on polynomial chaos expansion and genetic algorithm considering room occupant density [23].…”
Section: Exit Location Optimizationmentioning
confidence: 99%
“…If the total exit width is large, the pedestrian's travel distance to the exit becomes the main factor influencing the evacuation time [18]. As the distance between two adjacent evacuation doors increases (within the range of less than two body widths), the evacuation efficiency of the crowd decreases [19,20]. Further research by scholars has shown that both excessive and insufficient distances are not conducive to evacuation [21].…”
Section: Introductionmentioning
confidence: 99%
“…They incorporate customized user profiles to simulate the movement of handicapped and elderly people, and simulate a fire incident in a shopping center. Ma et al (2021) develop a simulation model that incorporates a pedestrian exit selection strategy model. Testing different exit designs, they discover that the total utilization of two exits drop if they are placed too close to each other, since the pedestrians may sway in choice between the two.…”
Section: Introductionmentioning
confidence: 99%